Health-related quality of life and complications of corticosteroid treatment in patients with immune thrombocytopenia in two teaching hospitals in Ethiopia: a cross-sectional study - Beyene, Dessale Abate; Sisay, Eskinder Ayalew; Fentie, Atalay Mulu; Gebremedhin, Amha (Frontiers in Medicine, 2024)
Background The treatment of immune thrombocytopenia (ITP) is a major clinical challenge and has a significant impact on health-related quality of life (HRQoL), and prolonged use of corticosteroids may have a negative impact on HRQoL. Objectives To evaluate the impact of ITP on HRQoL and complications of corticosteroid treatment in patients with ITP in two teaching hospitals in Ethiopia. Methods The institution-based cross-sectional study was conducted from November 15, 2022, to March 15, 2023, to recruit 214 study participants during the study period (4 months). The ITP Life Quality Index (ILQI) in the Amharic version was used to assess the impact of ITP. Linear regression analysis models were also used, and a p-value of less than 0.05 was generally considered statistically significant. Results Regarding treatment, the majority 172 (80.4%) of study participants were taking prednisolone only, and 143 (66.8%) of study participants had at least one side effect of corticosteroids during the entire treatment period. Predictive factors for a higher impact of ITP on HRQoL; all correlated variables explained 36.5% (adjusted R-squared = 0.365, p < 0.0001) of the variance and had a moderate impact on HRQoL. Furthermore, predictive factors for an increasingly higher impact of ITP on HRQoL were the development of emotionally related corticosteroid side effects (β = 0.392, 95% CI: 5.160–9.961, p < 0.001), the presence of fatigue during the assessment (β = 0.326, 95% CI: 4.394–9.475, p < 0.001), patients not taking cotrimoxazole prophylaxis treatment (β = 0.236, 95% CI: 2.236–6.570, p < 0.001), living far from the hematology clinic (outside Addis Ababa) (β = 0166, 95% CI: 1.107–5.114 p = 0.003), having epistaxis and/or wet purpura (mucosal bleeding) (β = 0.191, 95% CI: 0.091–4.259, p = 0.001), and skin symptoms (petechiae and ecchymosis) (β = 0.041, 95% CI: 0.091–4.259 p = 0.041) during diagnosis. Conclusion The impact of ITP on their energy levels and work life was high compared to the impact of ITP on daily life. The side effects of corticosteroids also affect the HRQoL of ITP patients.